Microwave wedge absorber design using rice husk - An evaluation on placement variation - Nornikman, Hassan; Soh, Ping Jack; Fareq, Malek, Dr.; Azremi, Abdullah Al Hadi; Wee, Fwen Hoon; R. Badlishah, Ahmad, Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2010)
Link to publisher's homepage at http://ieeexplore.ieee.org/